Совет ҳокимияти даврида қатағон органлар (SCIENCE and SOCIETY, 2025)
In this article, the revolutionary tribunals, the Supreme Revolutionary Tribunal and the extraordinary in- vestigation commissions established under it, played a special role among the repressive bodies. On November 18, 1918, the revolutionary tribunal of the Central Executive Committee of Turkestan was established, and under them, an investiga- tive commission and a jury of accusers were established.